The Cortical Silent Period in the Cricothyroid Muscle as a Neurophysiologic Feature for Dystonia Observation: E-Field-Navigated Transcranial Magnetic (TMS) Study - Konstantinović, Ivan; Bošković, Braco; Šoda, Joško; Dolić, Krešimir; Đogaš, Zoran; Lapčić, Mirko; Ledenko, Vlatko; Vrgoč, Toni; Rogić Vidaković, Maja (Biomedicines, 2023)
The cortical silent period (cSP) is a period of electrical silence following a motor-evoked potential (MEP) in the electromyographic signal recorded from a muscle. The MEP can be elicited by transcranial magnetic stimulation (TMS) over the primary motor cortex site corresponding with the muscle. The cSP reflects the intracortical inhibitory process mediated by GABAA and GABAB receptors. The study aimed to investigate the cSP in the cricothyroid (CT) muscle after applying e-field-navigated TMS over the laryngeal motor cortex (LMC) in healthy subjects. Then, a cSP as a neurophysiologic feature for laryngeal dystonia was observed. We applied a single-pulse e-field-navigated TMS to the LMC over both hemispheres with hook-wire electrodes positioned in the CT muscle in nineteen healthy participants, which triggered the elicitation of contralateral and ipsilateral corticobulbar MEPs. The subjects were engaged in a vocalization task, and then we assessed the following metrics: LMC intensity, peak-to-peak MEP amplitude in the CT muscle, and cSP duration. The results showed that the cSP duration from the contralateral CT muscle was distributed from 40 ms to 60.83 ms, and from the ipsilateral CT muscle, from 40 ms to 65.58 ms. Also, no significant difference was found between the contralateral and ipsilateral cSP duration (t(30) = 0.85, p = 0.40), MEP amplitude in the CT muscle (t(30) = 0.91, p = 0.36), and LMC intensity (t(30) = 1.20, p = 0.23). To conclude, the applied research protocol showed the feasibility of recording LMC corticobulbar MEPs and observing the cSP during vocalization in healthy participants. Furthermore, an understanding of neurophysiologic cSP features can be used to study the pathophysiology of neurological disorders that affect laryngeal muscles, such as laryngeal dystonia.